Attribute Amnesia in the Auditory Domain. (July 2021) - Howe, Piers Douglas Lionel; Lee, Serene Bee Wen
Individuals are often unable to report an attribute of an object to which they recently attended, if they expected to report a different attribute, a phenomenon known as attribute amnesia (AA). To date, all AA studies have occurred in the visual domain. The purpose of this study was to explore the boundary conditions of AA by testing if AA also occurs in the auditory domain and, if so, for which attributes. It was found that AA was present when reporting the location ( p  =   .003) and the number of tones ( p  <   .001) of an auditory stimulus, but not when reporting its pitch ( p  =   .383). These findings can be understood in terms of the organisation of the primary cortical areas and help explain the differences between visual working memory and auditory working memory.